Persepsi Masyarakat Mengenai Tingkat Kepentingan dari Tipe-tipe Penggunaan Lahan di Kawasan Taman Hutan Raya (Tahura) Bukit Barisan - Muhammad Ali Umar Siregar; Oding Affandi; Liliek Pudji Asmono (Program studi Kehutanan USU, 2014)
The close interrelation between forests and rural communities living around the forest was important in its development. Forest has an aspect of economics as need of the communities around the forest. The aim of this research was to determine people's perception of the importance of forests and land use as natural resources that exist in the communities around the Tahura Bukit Barisan, especially Doulu Village (Sub District of Berastagi) and Jaranguda Village (Sub District of Merdeka) Karo Regency. This research was conducted from April to May 2013. The method used Multidisciplinary Landscape Assessment (MLA), which is a combination of the Focus Group Discussion (FGD) and Pebble Distribution Method (PDM). To collect public perception, thi research used a list of questions. The number of samples required is 60 households, with details of 30 households each village. The results showed that the categories of land use was considered to be the most important was “housing area” according to male and female, with an average (31.5%) according to men and (33.6 %) according to women in the village of Doulu and Jaranguda. They need housing area importantly as village becouse it’s need to the center of economics activity, culture, education and social can be obtained.Keywords: Perception, Land use, MLA